Accidentally Broken Lateral Incisor Tooth at the Gingival Margin Treated by Endodontics, Cast Post and Core Finally Porcelain Jacket Crown: A Case Report (Bangladesh Journal of Dental Research & Education, 2015)
A successful treatment of a badly broken tooth in accidental case depends not only on good endodontic therapy but also on good prosthetic reconstruction of the tooth after the endodontic treatment is complete. In accidental case, sometimes it is found that there is very little or no clinical crown after root canal treatment. In such cases, additional retention & support of the restoration are difficult to achieve. In this case report endodontically treated tooth by suing cast post is discussed to achieve additional retention and supportBangladesh Journal of Dental Research and Education Vol.5(2) 2015: 73-74